The impacts of devolution policy for mangrove forest management in the Mekong River Delta - Mangrove and aquaculture in the Mekong River Delta, Vietnam - Truong, Dang Thuy (University of Gothenburg, 2021)
Mangrove forests are known to provide many ecological services and sources of livelihood to local community. The policy of contracting mangrove forest to households for management fails to conserve as farmers tend to convert mangrove to other uses. We proposed the following research objectives: [1] examine the impacts of devolution policy and other institutional measures on mangrove forest areas at commune level; [2] examine the impacts of devolution policies, institutional and economic factors on the mangrove coverage of mixed shrimp-mangrove systems. Mangrove forest indicators of analyses at both household and commune level in the South Vietnam are measured in two aforementioned ways. One is self-reported, by farm managers in household data and by Forestry Management in commune data, and the other is calculated using satellite images.

The survey was conducted in communes of six coastal provinces in the south of Vietnam, including Ben Tre, Soc Trang, Tra Vinh, Kien Giang, Ca Mau, and Bac Lieu. From these six provinces, eight locations were selected. Face to face survey was chosen, and each respondent was interviewed using a questionnaire of three parts, including general information of respondent, perception about mangrove of respondent, and aquaculture activities. We surveyed 659 mixed mangrove-shrimp farms. Mangrove forest indicators of analyses at both levels are measured in two ways. One is self-reported by farm managers in household data, and the other is calculated using satellite images. For calculating mangrove coverage of farms (mixed mangrove-shrimp farming system), coordinates of farms are collected during the survey. These coordinates are then used to create boundaries of farms on Google Earth.

Mangrove forests are known to provide many ecological services and sources of livelihood to local community. The policy of contracting mangrove forest to households for management fails to conserve as farmers tend to convert mangrove to other uses. We proposed the following research objectives: [1] examine the impacts of devolution policy and other institutional measures on mangrove forest areas at commune level; [2] examine the impacts of devolution policies, institutional and economic factors on the mangrove coverage of mixed shrimp-mangrove systems. Mangrove forest indicators of analyses at both household and commune level in the South Vietnam are measured in two aforementioned ways. One is self-reported, by farm managers in household data and by Forestry Management in commune data, and the other is calculated using satellite images.

The survey was conducted in communes of six coastal provinces in the south of Vietnam, including Ben Tre, Soc Trang, Tra Vinh, Kien Giang, Ca Mau, and Bac Lieu. From these six provinces, eight locations were selected. Face to face survey was chosen, and each respondent was interviewed using a questionnaire of three parts, including general information of respondent, perception about mangrove of respondent, and aquaculture activities. We surveyed 659 mixed mangrove-shrimp farms. Mangrove forest indicators of analyses at both levels are measured in two ways. One is self-reported by farm managers in household data, and the other is calculated using satellite images. For calculating mangrove coverage of farms (mixed mangrove-shrimp farming system), coordinates of farms are collected during the survey. These coordinates are then used to create boundaries of farms on Google Earth.
The impacts of devolution policy for mangrove forest management in the Mekong River Delta - Mangrove and aquaculture in the Mekong River Delta, Vietnam
Keywords: forestry; skogsbruk; MANGROVES; land use; markanvändning; Environmental monitoring facilities; Anläggningar för miljöövervakning; Economics and Business; Ekonomi och näringsliv; Economy; Ekonomi; Environment; Miljö